Mn-Doped ZnSe quantum dots initiated mild and rapid cation exchange for tailoring the composition and optical properties of colloid nanocrystals: novel template, new applications. Issue 8 (6th February 2017) - Zhou, Zhi-Qiang; Yang, Li-Yun; Yan, Ren; Zhao, Jie; Liu, Yu-Qi; Lai, Lu; Jiang, Feng-Lei; Maskow, Thomas; Liu, Yi
Abstract : We develop a mild and ultra-fast two-step cation exchange strategy for introducing transition metal ions into quantum dots and detecting Cd 2+ and Hg 2+ . Abstract : Although cation exchange (CE) has been studied for many years and some mechanisms were proposed, there is still a knowledge gap in CE and problems such as the need for high temperature and it being time-consuming are still unaddressed. We developed a new mild strategy for CE by introducing a new ideal template and first applied this doping strategy to detect Cd 2+ and Hg 2+ . This strategy adopted Mn-doped ZnSe quantum dots (QDs) as the template and the introduction occurs via a two-step CE reaction: first Zn 2+ was partially substituted by X (X = Cd 2+, Hg 2+, Cu 2+, Ag + or Pb 2+ ), later Mn 2+ (in the deep structure of QDs) was substituted by X. Remarkably, Mn 2+ in the lattice can be easily substituted by a dopant and its replacement by a dopant helps to bury the metal ions. The ultra-fast introduction of Cd 2+ and Hg 2+ (70 minutes for Cd 2+ and 19 minutes for Hg 2+ ) was realized at room temperature; other metal ions such as Ag +, Cu 2+ and Pb 2+ can be buried at 50 °C. This mild reaction temperature offers a solution for introducing impurities without sacrificing the interfacial structure of nanocrystals. HRTEM, XPS and ICP measurements were applied to analyze the introduction process. Furthermore, the spectroscopic method was employed to analyze the introduction, migration and distribution of metal ions. Then, we proposed a mechanism for the chemical conversion of nanocrystals by CE. Through this strategy, full-color light-emitting doped QDs were fabricated. Strikingly, a new turn-on probe for the detection of Cd 2+ and Hg 2+ with improved selectivity was developed by adopting this doping strategy. The detection limit is 36 nM for Cd 2+ and 20 nM for Hg 2+, which is competitive with the limit of detection reported by other groups using QDs as sensors.